Genetska variabilnost in ohranjanje genskih virov lesnike (Malus sylvestris (L.) Mill.) v Sloveniji - Kišek, Mateja (visokošolska dela, 2021)
Genetic and morphological characteristics of European crab apple (Malus sylvestris (L.) Mill.) in the territory of Slovenia and Croatia were studied. We analysed 14 morphological characteristics on the leaves. Genetic analysis was performed using 10 microsatellite markers. The analysis of the population of European crab apple tree population has revealed a very high degree of genetic variability among European crab apple trees (HT = 0.77). The low fixation index (FIS = 0.08) combined with a high degree of differentiation (FST = 0.18) indicates a significant genetic distance between populations and a low rate of kin reproduction, typical of populations in glacial refugia. Based on morphological analysis, the studied trees were classified as European crab apple (56.52%), hybrids (39.12%) and domesticated apple (4.35%), based on genetic analysis, the classification differs: European crab apple (73.91%), hybrids (19.57%), domestocated apple (6.52%). Only 52 % of botanically identified European crab apples were identified as European crab apple based on genetic data, and we confirm that individual morphological characters are not completely reliable for species identification. There are two separate gene pools of European crab apple trees and domesticated apple with a number of trees with a genetic mixture of the two species. The only seed object for European crab apple in Slovenia is not suitable for forestry use. Niether the seed trees nor the seedlings are genetically unsuitable. We have prepared guidelines for the conservation of the European crab apple genetic stock and proposed appropriate silvicultural measures that could enable long-term existence and high genetic diversity.
Keywords: conservation of genetic resources; disertacije; dissertations; European crab apple; genetic varibility; genetska variabilnost; hibridizacija; hybridization; lesnika; Malus sylvestris (L.) Mill.); morfološka variabilnost; morphologic variability; ohranjanje genskih virov; Slovenia; Slovenija